Improved Numerical-Analytical Thermal Modeling Method of the PCB With Considering Radiation Heat Transfer and Calculation of Components’ Temperature - Yabin Zhang (IEEE Access)
The previous work relating to the numerical-analytical coupling method for steady-state thermal analysis of the laminated PCB structure is first briefly reviewed. The Fourier-series analytical solution of temperature and the finite volume method were linked together for thermally modeling the PCB. For further modeling the PCB with components, thermal-resistance parameters of the components are then used for correlating components’ temperatures with the variable arrays in the coupling equations. For further considering radiation heat transfer between the PCB and the ambient, an iterative method is proposed. The radiation-equivalent heat transfer coefficient for each surface cell and each component can be updated during the iteration. Moreover, for improving the efficiency, the multigrid strategy is integrated in the coupling method for generating discrete cells of three levels in the metal layer and PCB surface region. To testify the iterative method, the model of a simple one-layer structure is compared with that built in COMSOL Multiphysics. The modeling results of the PCB of a phantom DC-DC power supply under radiation heat transfer are also given and discussed, and the modeling accuracy is approximately derived based on Richardson’s extrapolation.